Accessibility in Virtual Learning Environment: Theoretical Approach. - Braga, Marta C. G.; Ulbricht, Vania R. (InfoDesign, 2007)
The paper presents the requisites of the Web accessibility that can guide instructional designer when of the choice of Virtual Learning Environments (VLE’s) used in the interaction of teachers and pupils in courses online and, through which pupils get in contact with contents, activities of learning and evaluations. The instructional design demands multiple knowledge and happens in the interaction with several areas, such as the interface design, the information architecture and others. The instructional designer is that one make the mediation between the pedagogical theories and the technology proposing strategies so that the objectives of the learning happen. He must center the strategies in the audience practicing the design for all. From the theoretical approach, the present work intends to collaborate to minimize the difficulties of access in VLE’s and assistant in the digital inclusion of users with inabilities.